2017
DOI: 10.1002/ange.201612504
|View full text |Cite
|
Sign up to set email alerts
|

Designed Spiroketal Protein Modulation

Abstract: Spiroketals are structural motifs found in many biologically active natural products,w hich has stimulated considerable efforts towardtheir synthesis and interest in their use as drug lead compounds.D espite this,t he use of spiroketals,a nd especially bisbenzanulated spiroketals,i n astructure-based drug discovery setting has not been convincingly demonstrated. Herein, we report the rational design of ab isbenzannulated spiroketal that potently binds to the retinoid Xr eceptor (RXR) therebyi nducing partial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The binding of agonists to NRs induces the structural changes in the C-terminal region, especially in helix 12, and bring it to the folded form to recruit a coactivator efficiently [6], whereas an antagonist binding stabilizes the same region in the extended form by establishing a tetrameric structure [21]. Unlike a 'folded' type homodimer structure identified for a partial agonist-bound hRXRa-LBD in a recent study [25], the crystal structure of the hRXRa-LBD/CBt-PMN complex reported here has a tetrameric structure with an extended form of C-terminal helix with the ligand in two different rotational conformations. The conformation of CBt-PMN in subunit A1 is similar to that of bexarotene in the 'folded' form of hRXRa and the MD simulations clearly indicate that the conformation of the C-terminal helix changes to the folded form immediately in this subunit (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding of agonists to NRs induces the structural changes in the C-terminal region, especially in helix 12, and bring it to the folded form to recruit a coactivator efficiently [6], whereas an antagonist binding stabilizes the same region in the extended form by establishing a tetrameric structure [21]. Unlike a 'folded' type homodimer structure identified for a partial agonist-bound hRXRa-LBD in a recent study [25], the crystal structure of the hRXRa-LBD/CBt-PMN complex reported here has a tetrameric structure with an extended form of C-terminal helix with the ligand in two different rotational conformations. The conformation of CBt-PMN in subunit A1 is similar to that of bexarotene in the 'folded' form of hRXRa and the MD simulations clearly indicate that the conformation of the C-terminal helix changes to the folded form immediately in this subunit (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, hRXRα‐LBD bound to partial agonists have been shown to have a dimer form with a ‘folded’ AF‐2 interface , similar to that of the typical agonist‐bound structure. Unfortunately, the dynamics of the AF‐2 interface, whose conformation plays the most important role in the transactivity of RXR, remains not completely clear although a few studies in the past made considerable progress .…”
mentioning
confidence: 98%
See 1 more Smart Citation